Regulation of translocated c-myc genes transfected into plasmacytoma cells. - Feo, S (1986)
We have transfected two translocated c-myc oncogene clones, derived from two human lymphomas carrying the t(8;14) chromosome translocation, into mouse plasmacytoma cells to study the regulation of their expression. In one case, the transfected clone contained the two coding exons of the c-myc oncogene translocated to an immunoglobulin heavy-chain switch region; in the other case, the two coding exons were translocated 5' of the enhancer element located between the heavy-chain joining region (JH) and the switch region S mu. Nuclease S1 protection experiments indicate that only the c-myc translocated 5' of the enhancer element is transcribed in the plasmacytoma cells. Thus, 5'-truncation of the c-myc gene per se does not lead to c-myc deregulation. Further, since the level of c-myc transcripts in the parental human lymphoma cells was 3- to 4-fold higher than in the transfectants, it seems likely that additional elements within the heavy-chain locus may play a role in the enhancement of c-myc gene transcription in lymphoma cells.